2003
DOI: 10.1176/appi.ajp.160.11.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Mandatory Depression Screening of Dementia Patients in Nursing Homes

Abstract: Mandatory depression screening can significantly increase the proportion of depressed dementia patients receiving antidepressants, lead to dose adjustments, diminish potential ethnic biases in treatment, and affect the depressive symptoms of treated individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…Whites are more likely than nonwhites to be given antidepressant medications. Depression screening has been shown to significantly increase the number of nonwhite depressed dementia patients receiving antidepressant medications (Cohen, Hyland, & Kimhy, 2003).…”
Section: Use Of Medicationsmentioning
confidence: 99%
“…Whites are more likely than nonwhites to be given antidepressant medications. Depression screening has been shown to significantly increase the number of nonwhite depressed dementia patients receiving antidepressant medications (Cohen, Hyland, & Kimhy, 2003).…”
Section: Use Of Medicationsmentioning
confidence: 99%
“…Depression has been reported to be underdetected and undertreated in nursing homes, especially among residents with dementia (Burrows et al, 1995;Teresi et al, 2001;Cohen et al, 2003;Gruber-Baldini et al, 2005). Bagley et al (2000) found low rates of recognition of depression by nursing and other care staff in long-term care facilities (15-27%, depending on the definition of depression used).…”
Section: Introductionmentioning
confidence: 99%
“…There has been widespread under-recognition of depression in nursing homes, especially among residents with dementia (Burrows et al, 1995;Cohen et al, 2003;Gruber-Baldini et al, 2005). Bagley et al (2000) reported that nursing and other care staff recognized depression in 15-27% of cases (varying according to the definition of depression).…”
Section: Recognition Of Depression In Nursing Homesmentioning
confidence: 99%
“…Bagley et al (2000) reported that nursing and other care staff recognized depression in 15-27% of cases (varying according to the definition of depression). Studies in the U.S.A. showed that less than 25% of cases of depression in nursing homes were identified and treated (Cohen et al, 2003). Introduction of mandatory screening with the Cornell Scale for Depression in Dementia (CSDD; Alexopoulos et al, 1988) resulted in a significantly increased proportion of depressed dementia patients receiving antidepressants (44% versus 20%; Cohen et al, 2003).…”
Section: Recognition Of Depression In Nursing Homesmentioning
confidence: 99%